Os resultados e limites do consórcio como inovação organizacional no setor público subregional: o caso do CONSISAL - SAMPAIO, Sávio Cavalcante de Oliveira (2015)
This study had as objective to investigate the results and limits of the consortium as organizational innovation, in the municipal public sector, through the case of study of the CONSISAL. To achieve this, it was presented the contextualization of the consortium region, abording the characteristics which served as the foundation for its constitution. In the theoretical framework, the concept of consortium in the public sphere was based on the evolution of the Brazilian legislation. According to this, consortium carries innovative features to the counties. This, it was approached the concept of innovation with focus on public sector, and were used Oslo Manual (2006), Tigre (2006), Farah (2007), among other works as references. The methodology used is exploratory and based on a single case of study that was made through documentary research, direct observation, interviews; besides the use of questionnaires with municipal representatives to assess the "quantitative and qualitative impacts" and the "limits" of the innovative actions of the consortium. The analysis showed that the CONSISAL it’s an organizational innovation with focus on external relations of the consortium cities. Its impacts are more geared to access water for human consumption and for income generation. In the conception of cities members the degree of efficiency of impacts /results CONSISA was "positive" with the main focus on "social area" followed by "economic" and finally "environmental". Finally, the municipal representatives identified that the level of influence of the limiting factors of the consortium is "positive", and highlight firstly on 'institutional', accompanied by the "economic" and then the "technical".